The extent to which fourth-grade students possess scientific sense skills (A field study in the schools of the basic education stage in the city of Lattakia) - نصور , رغداء; نايف الدرويش , قمر جمال (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the research is to monitor the reality of scientific sense skills in the schools of the basic education stage, in terms of the extent of possession of Students of the fourth grade of basic science sense skills. To achieve this, the descriptive approach was used, and a test of scientific sense skills was prepared, where its validity and reliability were confirmed. It includes three skills. The test was distributed to a sample of the fourth grade students, who numbered (238) male and female students. The results of the research showed that the research sample possesses the skills of scientific sense with an average grade, equal to the hypothetical average level (2.5), i.e. 60% Thus, there is no difference between the calculated average of the students’ estimates about the two axes of the test (the extent of the ability to activate the majority of the senses, and the skill of thinking about thinking) and the hypothetical average of skills, while the results indicated that there was a statistically significant difference between the averages of the students’ estimates about the ability to retrieve information and link it to the present . The research ended with a set of proposals, such as the need to pay attention to the development of scientific sense skills among students of the basic education stage when they are presented in the curricula.